Jurnal rekayasa proses submission update - Petrus, Himawan Tri Bayu Murti (Jurnal Rekayasa Proses, 2023)
Aiming to be able to provide much better service and scientific publishing media for all related stakeholders, Jurnal Rekayasa Process is excited to bring you some important updates. First, we would like to inform you that we have transitioned to a new submission platform. We will no longer be accepting submissions through the old page https://jurnal.ugm.ac.id/jrekpros. Instead, we encourage all authors and researchers to utilize our new and improved submission platform at https://jurnal.ugm.ac.id/v3/jrekpros. Your cooperation in adhering to this change is highly appreciated, and we believe that this update will contribute to a more efficient submission process for everyone involved. Furthermore, we are pleased to announce a change in our publication schedule. Starting from the year 2024, the Journal Rekayasa Proses will publish three issues a year, specifically in April, August, and December. We trust that this adjustment will facilitate a more comprehensive and timely dissemination of valuable research. We sincerely appreciate your attention to these updates and your continued support. If you have any questions or concerns, feel free to reach out to our editorial team.